Emprendimiento social en Bogotá del juego de mesa Ambora (2024)
The Ambora project presents the development of a board game that addresses the issue of armed conflict in Colombia, specifically focusing on the experiences of the community in Buenaventura. Through innovative mechanics based on Dilemma-Driven Design and emotion theory, the game aims to raise awareness among university students in Bogotá about the realities of conflict in other regions of the country